Temporal Trends in Percutaneous Coronary Intervention and Coronary Artery Bypass Grafting: Insights From the Washington Cardiac Care Outcomes Assessment Program. Issue 11 (2nd June 2020) - Kataruka, Akash; Maynard, Charles C.; Kearney, Kathleen E.; Mahmoud, Ahmed; Bell, Sean; Doll, Jacob A.; McCabe, James M.; Bryson, Chistopher; Gurm, Hitinder S.; Jneid, Hani; Virani, Salim S.; Lehr, Eric; et al.
Abstract : Background: Patient selection and outcomes for percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) have changed over the past decade. However, there is limited information on outcomes for both revascularization strategies in the same population. The study evaluated temporal changes in risk profile, procedural characteristics, and clinical outcomes for PCI‐ and CABG‐treated patients. Methods and Results: We analyzed all PCI and isolated CABG between 2005 and 2017 in nonfederal hospitals in Washington State. Descriptive analysis was performed to evaluate temporal changes in risk profile and, risk‐adjusted in‐hospital mortality. Over the study period, 178 474 PCI and 36 592 CABG procedures were performed. PCI and CABG volume decreased by 2.9% and 22.6%, respectively. Compared with 2005–2009, patients receiving either form of revascularization between 2014 and 2017 had a higher prevalence of comorbidities including diabetes mellitus and hypertension and dialysis. Presentation with ST‐segment–elevation myocardial infarction (17% versus 20%) and cardiogenic shock (2.4% versus 3.4%) increased for patients with PCI compared with CABG. Conversely, clinical acuity decreased for patients receiving CABG over the study period. From 2005 to 2017, mean National Cardiovascular Data Registry CathPCI mortality score increased for patients treated with PCI (20.1 versus 22.4, P <0.0001) and decreased for patients treated with CABG (18.8 versus 17.8, P <0.0001). Adjusted observed/expected in‐hospital mortality ratio increased for PCI (0.98 versus 1.19, P <0.0001) but decreased for CABG (1.21 versus 0.74, P <0.0001) over the study period. Conclusions: Clinical acuity increased for patients treated with PCI rather than CABG. This resulted in an increase in adjusted observed/expected mortality ratio for patients undergoing PCI and a decrease for CABG. These shifts may reflect an increased use of PCI instead of CABG for patients considered to be at high surgical risk.